EVALUATING THE SCALE FACTORS OF PEDO-TRANSFER MODELING THE SOIL WATER CHARACTERISTIC CURVE OF ZAKHO SOILS - ABDULKHALIQ, NAJDAT SABRI (Journal of Duhok University, 2017)
The soil-water characteristic curve is the basis for estimating unsaturated soil properties. The negative pore pressure measurement is costly, time consuming, and needs accurate techniques to be measured. However, the pedo-transfer modeling of Arya and Paris introduces solution for the problem. The constant, linear, and Vaz scaling techniques in association with Arya and Paris model was used to predict SWCC from particle-size distribution.  A total of 48 soil suction vs. volumetric water content experimental tests representing the SWCC for five different regions of Zakho district was processed for this purpose. The scaling parameters were obtained and the results show that linear and constant techniques have interpret the experimental results of the SWCC with appreciable confidence, however Vas scaling method is not recommended to be used for Zahko soil for the relatively weak correlations obtained.